Women Nurturing Water, Land, and Family: a Study of Food Security in Ogan Komering Ilir South Sumatera - Yuliana, Sri (Yayasan Jurnal Perempuan, 2015)
Women at Air Sugihan are unique. They are able to sustain life under harsh natural conditions. Red swamp water, uncultivated peat lands, ashes from the burned forest as a result of simple and cheap land clearing techniques; as well as debt bondage as a cash-advanced to finance the farm-production activities which then aggravated their SRHR (sexual and reproductive health and rights), substantive health care and access to nutrition. This makes women at Air Sugihan struggled within harsh nature condition for the survival of their families for the sake of food security and for sustainable nature and environmental conservation. Starting from very limited experience to live in harsh condition, women reduce the family burden of living in poverty by sustaining water, land and family-economy.